2008
DOI: 10.1111/j.1365-2702.2008.02432.x
|View full text |Cite
|
Sign up to set email alerts
|

‘A pacemaker in my heart’– classification of questions asked by pacemaker patients as a basis for intervention

Abstract: Pacemaker implant guidance should be based upon experimental evidence, arranged according to each category's relative weight and take into account the patient's point of view.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Moreover, the patients’ biopsychosocial adjustment after PPM implantation plays an important role in determining their QoL. Rassin, Zilcha, and Gross (2009) found that patients ( n = 123) often felt stressed about daily activities such as swimming, lifting, and using a smartphone or electric razor after PPM implantation. Aqeel, Shafquat, and Salahuddin (2008) reported that most patients with PPMs ( n = 93) considered daily activities such as driving a car, passing through metal detectors, bending over, sleeping on the side with the PPM, or using electronic products unsafe.…”
Section: Background and Rationalementioning
confidence: 99%
“…Moreover, the patients’ biopsychosocial adjustment after PPM implantation plays an important role in determining their QoL. Rassin, Zilcha, and Gross (2009) found that patients ( n = 123) often felt stressed about daily activities such as swimming, lifting, and using a smartphone or electric razor after PPM implantation. Aqeel, Shafquat, and Salahuddin (2008) reported that most patients with PPMs ( n = 93) considered daily activities such as driving a car, passing through metal detectors, bending over, sleeping on the side with the PPM, or using electronic products unsafe.…”
Section: Background and Rationalementioning
confidence: 99%
“…It was observed that lack of information or misinformation may result in self-imposed restrictions that can adversely affect ordinary activities and create hesitancy about electrical items found in the house setting [ 20 , 21 ]. It was demonstrated that the most frequent question directed to healthcare providers was related to the motion and effort that was followed by environmental influences [ 9 11 , 22 ]. In fact, both PMs and ICDs have a risk of device malfunction related to external factors leading to morbidity, mortality, or device replacements; moreover ICDs have a risk of giving inappropriate shocks [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meaning-centered needs in conversation about CVD with doctors and nurses 4 Schaufel et al, 2009;Kohlmann et al, 2013;McClung, 2013;Strang et al, 2013;Barello et al, 2015 Meaning-centered changes and needs after CVD event 30 Mårtensson et al, 1998;Popogrebsky, 1998;Clarke et al, 1999;Nilsson et al, 1999;Ecochard et al, 2001;Davidson et al, 2003;Secrest and Zeller, 2003;Faircloth et al, 2004;Lobeck et al, 2005;Secrest and Zeller, 2006;Cortis and Williams, 2007;Leegaard and Fagermoen, 2008;Schou and Egerod, 2008;Wann-Hansson et al, 2008;Bremer et al, 2009;Hefferon et al, 2009;Rassin et al, 2009;Eilertsen et al, 2010;Kutner, 2010;Silva et al, 2011;Lawrence and Kinn, 2012;Andersson et al, 2013;Ross and Austin, 2013;Junehag et al, 2014;Leeming et al, 2014;Buck et al, 2015;DuBois et al, 2015;Hansen et al, 2016;Satink et al, 2016;Littooij et al, 2016.…”
Section: Joel Vosmentioning
confidence: 99%